2020
DOI: 10.1002/pen.25470
|View full text |Cite
|
Sign up to set email alerts
|

Poly‐3‐hydroxybutyrate‐based constructs with novel characteristics for drug delivery and tissue engineering applications—A review

Abstract: Herein, we reviewed polymeric constructs of polyhydroxyalkanoates (PHAs) at large and poly‐3‐hydroxybutyrate (P3HB), in particular, for drug delivery and tissue engineering applications. Polymeric constructs that can efficiently respond to numerous variations in their surroundings have gained notable attention from different industrial sectors such as biomedical, clinical, pharmaceutical, and cosmeceutical. Among them, considerable importance is given to their drug delivery and tissue engineering applications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 110 publications
1
24
0
Order By: Relevance
“…[19] The resulting torque vs time curves were plotted and compared with the neat polymer. The mechanical energy (E m ) (kJ kg −1 ) was calculated from the curves using Equation (1):…”
Section: Melt Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] The resulting torque vs time curves were plotted and compared with the neat polymer. The mechanical energy (E m ) (kJ kg −1 ) was calculated from the curves using Equation (1):…”
Section: Melt Processingmentioning
confidence: 99%
“…Poly(hydroxybutyrate‐ co ‐hydroxyvalerate) (PHBV) is a biodegradable and biocompatible random copolymer of natural origin with a great interest as a substitute for conventional thermoplastics in several applications, including packing industry, drug delivery, tissue engineering, among others. [ 1 ] However, PHBV is sensitive to high temperatures and shear stresses associated with melt processing. [ 2 ] Both of these factors cause a drastic reduction in molecular weight, although it is reported that a pretreatment of the polymer in the synthesis process or prior to the melt processing might promote an improvement on its thermal and chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Drugs can be administered via oral, parenteral (intramuscular, subcutaneous, intrathecal, and intravenous), rectal, sublingual/ buccal, vaginal, ocular, nasal, transdermal, or via inhalation. [1,4] Compared with ordinary dosage methods (ie, oral ingestion and intravenous injection), the controlled release formulations display more precise dosage control, decrease side effects, and reduce dosages of drug necessary to induce similar therapeutic effects, improving patient compliance and convenience. [5] The release effectiveness of the encapsulated drug depends on its loading efficacy and release mechanisms, including the swelling, diffusion, desorption, and degradation of the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…An array of multi-functional biomaterials is evolving with enormous curiosity for researchers due to their range of applications. Research is underway around the globe to engineer pristine or hybrid polymer-based bio-composites that plays a substantial role in a field of catalysis, enzymology, environmental, pharmaceutical, and biomedical applications [1][2][3][4][5] . Bio-composites can be engineered using naturally occurring biopolymers either in pristine form or the combination of multi-materials.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, synthetic polymer-based bio-composites, nano-composites (based on pristine or hybrid biopolymers) also exhibit inherited or improved structural and multi-functional attributes, for example, biocompatibility, biodegradability, (re)generatability, renewability, recyclability, high and efficient functionality against various substrates, induced turn-over, and overall cost-effectiveness are of high interest for numerous applications. Individually or collectively, all those properties of bio-composites open new and interesting perspectives with notable incidences in the environmental, biomedical, and biotechnological sector of the modern-day world 5,[7][8][9] .…”
Section: Introductionmentioning
confidence: 99%